2023
DOI: 10.3390/horticulturae9010087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vernalization on Off–Season Flowering and Gene Expression in Sub-Tropical Strawberry cv. Pharachatan 80

Abstract: Off-season strawberry production may diversify the yield, thereby increasing costs, but the environmental conditions are a limiting factor. This experiment aimed to study the effects of vernalization on off-season flowering and gene expression in sub-tropical strawberry cv. Pharachatan 80. The factorial (2 × 2) + 1 in a completely randomized design was used in this study. Factor A was the vernalization temperatures: 2 °C and 4 °C. Factor B was the vernalization periods: 1 week and 2 weeks, compared with non-ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Strawberry cv. Pharachatan 80, the most popular variety, was developed by The Royal Project Foundation for commercial purposes [3]. Strawberry anthracnose is a common disease of strawberry production in the highland region of Chiang Mai, Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry cv. Pharachatan 80, the most popular variety, was developed by The Royal Project Foundation for commercial purposes [3]. Strawberry anthracnose is a common disease of strawberry production in the highland region of Chiang Mai, Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Strawberry plants vernalized at 2 °C for 2 weeks had the highest percentage of flowering, number of inflorescences, number of flowers per inflorescence and number of flowers per plant as compared to vernalized at 4 °C [24]. [25] also indicated that cooling of the crown to 10-20°C induced flower bud differentiation of June-bearing strawberries. Extreme high or low temperature effected on flower development pollination and fruit malformation in strawberry [26,27] Nowadays, climate change and global warming raise ambient and soil temperatures causing strawberry productivity to decline.…”
Section: Discussionmentioning
confidence: 81%